Սոցիալիստական ռեալիզմ (ծագման և զարգացման պատմության շուրջ) - Ռ. Կ. Միրզախանյան (ՀՀ ԳԱԱ հրատ.)
Метод социалистического реализма является одним из мировоззренческих методов государственного подхода к художественному творчеству. История развития определений соцреализма раскрывает концептуальную базу режимного, исключительно централизованного восприятия социальной миссии художника коммунистического строя. The paper considers one of the officially recognized and supported approaches of the State conception of the methods of artistic creativity, more precisely, the method of socialist realism which was politically preferable for the Soviet regime.
Keywords: Literature; H Social Sciences; Language and Literature; Socialism; Communism; Anarchism; N Fine Arts; NX Arts